Introduction: Bureaucratic Routes to Migration: Migrants' Lived Experience of Paperwork, Clerks, and Other Immigration Intermediaries - Karine, Geoffrion; Cretton, Viviane (Anthropologica, 2021)
For a number of migrant actors, bureaucratic processes related to immigration constitute the greater part of the route toward their aspired destination and significantly shape their experience of migration and forced immobility. This special issue takes a look at the meaningful ways in which migrant actors interact with immigration bureaucracies and at how administrative procedures, with their highly emotional potential, shape in turn the subjectivity, decisions and actions of migrant actors. All the articles here analyse immigration bureaucracy as a dynamic process mediated by a network of people and by material objects (for example, documents, forms). Whether work, marriage or refuge is the reason for migration, the period of waiting in administrative limbo — which can last years — is crucial to our understanding of the bureaucratic encounter as a social force. This issue, dedicated to migrants’ lived experience of paperwork, clerks and other immigration intermediaries, explores two aspects of migrant actors’ encounters with immigration bureaucracies that go beyond the specificities of each individual’s personal background and trajectory: the production of affects and bureaucratic agency; the former often being the driving force behind the latter.